1998
DOI: 10.1097/00005537-199809000-00025
|View full text |Cite
|
Sign up to set email alerts
|

Systemic neutrophil intrinsic 5‐lipoxygenase activity and CD 18 receptor expression linked to reperfusion injury

Abstract: Zileuton, a 5-LO inhibitor, reduces adhesion receptor expression on systemic neutrophils and attenuates i/r injury. Systemic neutrophil intrinsic 5-LO activity and CD18 receptor expression are linked to reperfusion injury and may be fundamental events in its pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…In mouse renal I/R model, Patel et al (28) demonstrated that degree of renal dysfunction and tissue injury was preserved along with reduced intercellular adhesion molecule-1 expression and neutrophil infiltration in kidneys in 5-LOX knockout mice and by treatment with 5-LOX inhibitor zileuton. These findings were in accordance with those of a previous study demonstrating that zileuton reduced CD18 adhesion receptor expression on systemic neutrophils and attenuated I/R injury in guinea pig skin flaps (29). In rat brain damage induced by cerebral ischemia, zileuton was found to be effective in reducing brain damage via decreasing MDA content, and inhibition of NF-kB and inducible nitric oxide synthase (iNOS) expression (30).…”
Section: Discussionsupporting
confidence: 93%
“…In mouse renal I/R model, Patel et al (28) demonstrated that degree of renal dysfunction and tissue injury was preserved along with reduced intercellular adhesion molecule-1 expression and neutrophil infiltration in kidneys in 5-LOX knockout mice and by treatment with 5-LOX inhibitor zileuton. These findings were in accordance with those of a previous study demonstrating that zileuton reduced CD18 adhesion receptor expression on systemic neutrophils and attenuated I/R injury in guinea pig skin flaps (29). In rat brain damage induced by cerebral ischemia, zileuton was found to be effective in reducing brain damage via decreasing MDA content, and inhibition of NF-kB and inducible nitric oxide synthase (iNOS) expression (30).…”
Section: Discussionsupporting
confidence: 93%
“…It has been shown that myocardial I/R promotes the release and metabolism of leukotrienes (LTs), which are metabolites of arachidonic acid formed from the 5-LOX pathway and exert potent vasoactive and proinflammatory effects (12). LTs also play roles in I/R of skin, brain, and kidney (8,11,34), and 5-LOX inhibitors have been suggested to be useful in the treatment of conditions associated with I/R of the kidney (34). However, the effects of 5-LOX inhibitors on mycardial I/R are rather controversial.…”
Section: Discussionmentioning
confidence: 99%
“…LTs are involved in the genesis of inflammation and edema, because of their effects on vascular permeability, plasma extravasation, and diapedesis of white blood cells [6,7], and they may also play an important role in adaptive immune responses [8]. There is now good evidence that LTs play a pivotal role in the pathophysiology of asthma [9,10] and psoriasis [11,12], as well as in conditions associated with ischemia-reperfusion (I/R) of skin [13,14], brain [15], and kidney [13,16,17]. LTs also play a physiological role in the host defense against microbial infections [18].…”
Section: Introductionmentioning
confidence: 99%